Refractive errors in children and young adults with Down's syndrome - Ljubic, Antonela; Trajkovski, Vladimir (Wiley, 2011)
Purpose: Down’s syndrome (DS) is the most common chromosomal anomaly. Numerous ophthalmic features have been reported. The aim of our study was to investigate the incidence of refractive errors in children and young adults with DS in Macedonia. Methods: Fifty-six children and young adults with DS, aged 2–28 years, from Macedonia, underwent slit-lamp examination, ocular motility and refraction. Results: The overall incidence of refractive errors in the Macedonian children and young adults with DS was 96.4%. A total of 17.8% of the subjects had myopia, 23.2% had hypermetropia and 55.3% had astigmatism. Strabismus was seen in 13 (23.2%) of the subjects (nine had esotropia, three had exotropia, one had hypertropia). Conclusions: The incidence of refractive errors in Macedonian children and young adults with DS was similar to that in Asian children. Compared with White (Caucasian) and Asian children with DS, Macedonian children and young adults exhibited lower incidences of hypermetropia and myopia, and a higher incidence of astigmatism, in which oblique astigmatism represented the predominant type.
Keywords: Down’s syndrome, refractive errors, astigmatism, strabismus